The ADAMTS18 gene is responsible for autosomal recessive early onset severe retinal dystrophy - Peluso Ivana; Conte Ivan; Testa Francesco; Dharmalingam Gopuraja; Pizzo Mariateresa; Collin Rob WJ; Meola Nicola; Barbato Sara; Mutarelli Margherita; Ziviello Carmela; Barbarulo Anna Maria; Nigro Vincenzo; et al. (Orphanet Journal of Rare Diseases, 2013)
Abstract Background Inherited retinal dystrophies, including Retinitis Pigmentosa and Leber Congenital Amaurosis among others, are a group of genetically heterogeneous disorders that lead to variable degrees of visual deficits. They can be caused by mutations in over 100 genes and there is evidence for the presence of as yet unidentified genes in a significant proportion of patients. We aimed at identifying a novel gene for an autosomal recessive form of early onset severe retinal dystrophy in a patient carrying no previously described mutations in known genes. Methods An integrated strategy including homozygosity mapping and whole exome sequencing was used to identify the responsible mutation. Functional tests were performed in the medaka fish (Oryzias latipes) model organism to gain further insight into the pathogenic role of the ADAMTS18 gene in eye and central nervous system (CNS) dysfunction. Results This study identified, in the analyzed patient, a homozygous missense mutation in the ADAMTS18 gene, which was recently linked to Knobloch syndrome, a rare developmental disorder that affects the eye and the occipital skull. In vivo gene knockdown performed in medaka fish confirmed both that the mutation has a pathogenic role and that the inactivation of this gene has a deleterious effect on photoreceptor cell function. Conclusion This study reveals that mutations in the ADAMTS18 gene can cause a broad phenotypic spectrum of eye disorders and contribute to shed further light on the complexity of retinal diseases.